2015
DOI: 10.1136/annrheumdis-2014-206417
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-124 inhibits the progression of adjuvant-induced arthritis in rats

Abstract: We found that miR-124 ameliorated AIA by suppressing critical prerequisites for arthritis development, such as RANKL and NFATc1. Thus, miR-124a is a candidate for therapeutic use for human rheumatoid arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 40 publications
3
59
0
Order By: Relevance
“…For example, Lee et al discovered that miR-124 inhibits osteoclastogenesis via NFATc [30,31]. However, much uncertainty still exists about the relation between miR-124 and osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lee et al discovered that miR-124 inhibits osteoclastogenesis via NFATc [30,31]. However, much uncertainty still exists about the relation between miR-124 and osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…miRNA-dependent mechanisms can turn off genes that promote monocyte differentiation to instead promote the differentiation of monocytes to mature, bone-resorbing osteoclasts [87]. Interestingly, it has been shown that treatment of rats with antigen-induced arthritis with miR-124 not only suppressed measures of inflammation, but also targeted critical mRNAs involved in osteoclastogenesis, including NFATc1 [88]. Further elucidation of bone-related pathways regulated by miRNAs in rheumatic diseases may provide new insights into pathogenesis, as well as new targets for therapy.…”
Section: Bone Resorption In Ramentioning
confidence: 99%
“…In osteoclasts, miR-124 can target NFATc1, key transcription factor; it also reduces osteoclast precursor proliferation and motility by targeting integrin B1 (ITGB1), RhoA and Rac1 [97]. In a rat inflammatory arthritis model, miR-124 mimic injection was shown to ameliorate progression of the arthritic lesion by decreasing osteoclast formation [100]. …”
Section: Mir-snps: Snps In Mirna Genes Altering Their Biogenesis Amentioning
confidence: 99%